A comparison between dextranomer/ hyaluronic acid and polyacrylate polyalcohol copolymer as bulking agents for treating primary vesicoureteral reflux - Alizadeh, Farshid; Omidi, Iman; Haghdani, Saeid; Hatef Khorrami, Mohammad; Izadpanahi, Mohammad Hossein; Mohammadi Sichani, Mehrdad (Urology Journal, 2019)
Purpose: In recent years, endoscopic subureteral injection has gained popularity as a therapeutic alternative to open surgery because of its high success rates and low morbidity. We compared the success and complication rates of Polyacrylate polyalcohol copolymer (PPC) and Dextranomer/Hyaluronic acid (Dx/HA) in the endoscopic treatment of VUR. Materials & Methods: We retrospectively reviewed the patients who underwent endoscopic correction of their VUR by subureteric injection of PPC or Dx/HA from Jan 2010 to April 2016. The injection technique was STING (subureteric), distal HIT (intraureteric), and double HIT according the hydrodistention (HD) grade. The success rate, injection technique, injection volume, VUR grade, and obstruction rate were evaluated and compared between two groups. Results: 107 renal refluxing units (RRU) with a mean age 55.23±36.58 months and 64 RRU with a mean age 52.13±31.66 months were treated in Dx/HA and PPC groups, respectively. The PPC group showed a more successful outcome in comparison to the Dx/HA group (92.2% versus 75.7% of the RRU with P value<0.001) at 3 months follow up. The injection technique was not significantly different between two groups. In PPC group the success rate was decreased significantly with increasing reflux grade but this reduction was not statistically significant in Dx/HA group. The injected volume was significantly more in PPC group; in addition, there was statistically significant correlation between injected volume of the bulking agent and obstruction rate. However, the obstruction rate did not establish significant difference between the two groups (P value=0.83), however it was earlier in Vantris (4 months versus 22 months). Conclusions: Our investigation approved PPC as a more effective material, regardless of other confounding variables such as reflux grade, learning cure, and technique of injection, in endoscopic treatment of VUR. In addition, the other remarkable point is this effectiveness is not accompanied by more post-operation obstruction.